Wczesnoceramiczny kompleks jelszański w międzyrzeczu Wołgi i Uralu. Aspekt chronologiczny - Reszel, Maciej (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
As a result of the last decade comprehensive studies on the chronology of the Yelshanian Culture, some spectacular results of radiocarbon dates were achieved. According to these data, the beginnings of ceramic cultures („Neolithic”1) of the Mid-Volga Region have been dated back to the second half of the 8th millennium BC.
The early pottery Yelshanian complex of the Volga-Ural interfluve. The chronological aspect